Frequency of outcomes of patients with pregnancy of unknown location at a tertiary care hospital. - Rabia Wajid, Amna Ahsan, Razia Riaz, Mazhar Abbas, Munaza Noor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A pregnancy of unknown location (PUL) is said to occur when empty uterus is seen on a Transvaginal Scan in a female with a positive pregnancy test with absence of signs of an intrauterine pregnancy (IUP) or an ectopic pregnancy. Aim: To determine the frequency of outcomes of patients with pregnancy of unknown location at a tertiary care hospital. Methods: The study was carried out at Department of Obstetrics &Gynecology, Lady Willingdon hospital, Lahore. It was a Descriptive case series conducted from 2021 to May 2022. 160 subjects meeting the inclusion criteria were enrolled in the study. A thorough history was obtained and levels of serum Beta-HCG recorded. Serum beta HCG levels of 25IU/L represented a positive pregnancy test. The follow up consisted of monitoring serum beta HCG levels after 48 hours and evaluation of findings of transvaginal ultrasound. The females were followed till they were placed in the category of failing PUL, an intrauterine pregnancy or an ectopic pregnancy. Data was collected from women categorized as having a PUL. Results: In this trial, of 160 cases, it was seen that 109(68.13%) had amenorrhea whereas 51(31.87%) had bleeding at the time of presentation. Frequency of outcomes of patients with pregnancy of unknown location showed that 75(46.88%) had failing PUL, 19(11.87%) had ectopic pregnancy, 15(9.38%) had persistent PUL and 51(31.87%) had intrauterine pregnancy. Conclusion: Failing PUL was the leading entity in cases of pregnancy of s unknown location followed by ectopic pregnancy and persistent PUL. However, this data is primary and needs validation through some other local trials. Keywords: Pregnancy of unknown location, outcome, failing PUL, ectopic pregnancy, persistent PUL